TOSHKENT VILOYATI OILALARIDA AJRALISH JARAYONI VA UNING GEODEMOGRAFIK JIHATLARI - Sh.Sabirova, M. (SCIENCE and SOCIETY, 2024)
This article talks about the process of divorce in the families of residents of the Tashkent region, its socio-demographic and geographical factors, and the territorial differences in the process of divorce of the residents of the region by villages and cities.